Cardiomyopathy Does Not Exacerbate the Severity of Pneumonia Caused by a SARS-CoV-2 Delta Variant in the J2N-k Hamster Model - Iwatsuki-Horimoto, Kiyoko; Ito, Mutsumi; Okuda-Hamabata, Moe; Takagi, Hisayoshi; Imai, Masaki; Kawaoka, Yoshihiro (Viruses, 2023)
Cardiovascular disease is one of many risk factors that have been linked to increased severity or mortality in coronavirus disease 2019 (COVID-19) patients; however, the exact role of SARS-CoV-2 in the pathogenesis of cardiac inflammatory injury has not been established. A previous study reported that SARS-CoV-2 causes more severe disease with cardiomyopathy in a J2N-k animal model. Here, we investigated the sensitivity of J2N-k hamsters, as a cardiomyopathy animal model, to a delta strain of SARS-CoV-2 compared to J2N-n control animals. We found that J2N-k hamsters were less susceptible to this delta strain than J2N-n animals, and we found no evidence that cardiomyopathy is a risk factor in this animal model. Since the previous study reported that SARS-CoV-2 causes more severe disease with cardiomyopathy in the same animal model, further analysis of the relationship between cardiomyopathy and SARS-CoV-2 infection is needed.